Palm Sap Innovation as Bacterial Cellulose Material - Wardatul Husna Irham; Sri Wahyuna Saragih; Saroha Manurung; Christine Gabriela; Ariel Ramadani; Trisna Anggraeni (Jurnal Penelitian Pendidikan IPA, 2026)
Old palm oil trunk waste produces sap water which is currently being developed only for the production of brown sugar. Palm oil trunk waste sap has great potential as another material. This study conducted the synthesis of bacterial cellulose from palm sap and conducted a characterization test of bacterial cellulose from the palm sap. This study is classified as qualitative research with laboratory research methods. The results of the study showed the success of palm sap as a bacterial cellulose material, with an optimal formation time on the 10th day with a thickness of 2.5 cm and an absorption capacity of 137.5 g/g. The FTIR test results showed specific functional groups of cellulose, namely OH at the peak of 3290 cm-1, aromatic C-C bonds at the peak of 1561 cm-1, CO bending bonds at the peak of 1399 cm-1 and H stretching vibrations with CO bonds at the peak of 1072 cm-1 and a closed chain was seen at the fingerprint peak. The SEM test showed a branched pellicle morphology that was bound long and strong. Mechanical tests showed an elongation at breaking load of 25.841%. XRD tests showed specific characteristics of pure cellulose at diffraction peaks of 14.20 and 15.40.